2020
DOI: 10.1007/s00374-020-01487-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon use efficiency and microbial functional diversity in a temperate Luvisol and a tropical Nitisol after millet litter and N addition

Abstract: Tropical soils often contain less soil organic C (SOC) and microbial biomass C (MBC) than temperate soils and, thus, exhibit lower soil fertility. The addition of plant residues and N fertilizers can improve soil fertility, which might be reflected by microbial C use efficiency (CUE) and functional diversity. A 42-day incubation study was carried out, adding leaf litter of the C4 plant finger millet (Eleusine coracana Gaertn.) and inorganic 15N fertilizer. The aim was to investigate amendment effects on CUE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 89 publications
1
10
0
1
Order By: Relevance
“…Soil microbial diversity is closely related to microbial stability, soil quality, and nutrient cycles and is susceptible to the input of exogenous organic matter ( Schroeder et al, 2020 ; Xu et al, 2021 ). Generally, the increase in resource availability under litter addition treatments contributes to the growth of individual microorganisms ( Storch et al, 2018 ), thus increasing soil microbial diversity ( Dilly et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial diversity is closely related to microbial stability, soil quality, and nutrient cycles and is susceptible to the input of exogenous organic matter ( Schroeder et al, 2020 ; Xu et al, 2021 ). Generally, the increase in resource availability under litter addition treatments contributes to the growth of individual microorganisms ( Storch et al, 2018 ), thus increasing soil microbial diversity ( Dilly et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…litter, respectively, using the POM recovery approach (Joergensen and Wichern 2018). Schroeder et al (2020) also observed no effect of N fertilization on CUE, but a strong true priming effect on SOM (Kuzyakov et al 2000), apparently not caused by N mining, as N fertilization affected neither CUE nor SOM priming. This might be different for plant residues differing in their C/N ratio, especially at different temperatures, which has not been tested by the POM recovery approach (Joergensen and Wichern 2018) until now.…”
Section: Introductionmentioning
confidence: 70%
“…Positive (Oliver et al 2021;Soares and Rousk 2019) and negative relationships (Manzoni et al 2017;Xiao et al 2021) have been reported between the litter C/N ratio and CUE vales. However, Lukas et al (2019) and Schroeder et al (2020) did not find any effect of soil type on the CUE of maize (Zea mays L.) and finger millet (Eleusine coracana Gaertn.) litter, respectively, using the POM recovery approach (Joergensen and Wichern 2018).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Em ecossistemas temperados os solos contem mais carbono orgânico e nutrientes minerais do que os solos de clima tropical, e portanto, apresentam maior fertilidade (SCHROEDER et al, 2020). As vezes, um excesso de nutrientes é uma preocupação maior com muitos solos temperados sob agricultura, enquanto ao aumento da fertilidade do solo é um importante tópico de pesquisa atual em muitas regiões tropicais (LIZCANO et al, 2017).…”
Section: Introductionunclassified